A Narrative Inquiry of The English Teachers in Teaching English Vocabularies Using Islamic Songs at State Islamic Junior High School - Azizah Rasyid; Ratna Dewi; Nur Qalbi (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2022)
This research aimed at finding out the teachers’ teaching vocabularies process using Islamic songs at MTsN 2 Makassar, and the reflection of the teachers’ experiences in teaching vocabularies using Islamic song. This research employed a qualitative method focused on narrative inquiry data with 2 subjects of English teachers at MTsN 2 Makassar chosen through purposive sampling method. The data were collected by using interview and observation and it was analyzed by using Miles and Huberman theory. The results of this research revealed that the teachers had different ways in teaching vocabularies classified into four phases: 1) class preparation was based on the lesson plan they made, prepared the song, the task, additional materials, and media. One of the teachers suggested that the category of Islamic songs is not always determined by the song sung by Muslims, yet the messages can be associated with Islamic view; 2) Pre-teaching, the teachers did warming up and stimulated the students to lead to the main activity; 3) whilst teaching, the teachers did main activities by using media, proper strategies, found out the moral value, and assessed the students; and 4) post-teaching, they concluded, motivated, and gave homework. The reflection showed that inhibited factors were the students’ lack of motivation, inadequate infrastructure, unsuitable media, big number of students, got difficulty in pronouncing, classifying and stuck with unfamiliar words, lack of confidence and felt afraid of making mistakes. Moreover, similar results appeared on how they engaged the students to obtain the moral message from the songs such as thanking to God and He is always with us. Conversely, they had dissimilar reflections in evaluating their strengths and weaknesses. The researchers recommend to use Islamic song to inspire the students about part of speech, the moral message, or choose general song containing of Islamic view.